Strategi Pengelolaan Infrastruktur Pesantren untuk Peningkatan Kualitas Pembelajaran di Pondok Pesantren Tarbiyatul Nurul Iman Bantur Malang - Widodo, Wahyudi (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
In the progress of education and learning in Islamic boarding schools, it is inseparable from good infrastructure management and in accordance with the objectives. Therefore, the infrastructure management strategy must be appropriate. The purpose of this study is to describe the strategy of managing pesantren infrastructure related to education and learning. This research method qualitative with a descriptive analysis approach. The results obtained are that the pesantren infrastructure management strategy has 3 things in general, namely: educational planning, the implementation of education at each level, and educational evaluation. Meanwhile, there are two supporting strategies for infrastructure management, including: the management of financial revenues for infrastructure and the management of the implementation of infrastructure development. As a result of this good infrastructure management strategy, the Tarbiyatul Nurul Iman Islamic Boarding School related to the quality of education and learning has greatly improved. This is evidenced by the existence of an Islamic boarding school program that is open to the public. The schools start from PAUD, RA, MI, and special night madrasah schools. Likewise in learning, each school already has its own building, and has complete facilities such as sports venues, extracurriculars, classrooms, libraries and training centers until they are equipped with modern technology.